REMOVED: MeCP2-chromatin binding dynamics shows a direct genotype–phenotype correlation in males with single amino acid substitutions. Issue 47 (December 2015) - Sheikh, Taimoor; Faghfoury, Hannah; Silver, Josh; Vincent, John B.
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ) This meeting abstract has been removed by the Publisher. Due to an administrative error, abstracts that were not presented at the ISDN 2014 meeting were inadvertently published in the meeting's abstract supplement. The Publisher apologizes to the authors and readers for this error.